TEACHING ARGUMENTATION IN READING AND LINGUISTIC ANALYSIS PROCESSES AT BASIC EDUCATION - Nascimento, Erivaldo Pereira do (Laboratório Editorial FCL-UNESP, 2016)
In this paper, we discuss the matter of teaching argumentation phenomenon at basic education, aiming to demonstrate how to teach argumentation in reading and linguistic analysis processes, based on a discursive and linguistic conception of this phenomenon of the human language. Therefore, it is a reflexive and propositional work based on two theoretical currents: The Discourse Argumentation Theory, proposed by Perelman (1999), and the Theory of Argumentation in the Language-System, by Ducrot and his collaborators (1987, 1988, 1994). In this paper, we will show more specifically how it is possible to work argumentative abilities and strategies, at different discourse genres, in the classroom, taking into consideration, among other things, both rhetorical and linguistic argumentative strategies that are more frequent in a specific genre and the relationship between content and argumentation.  Finally, we will show some activities of linguistic analysis, which the functioning of determined argumentation strategies is observable in the linguistic system.